1996
DOI: 10.1002/elps.1150170207
|View full text |Cite
|
Sign up to set email alerts
|

Indirect UV detection of carbohydrates in capillary zone electrophoresis by using tryptophan as a marker

Abstract: A rapid and sensitive method for the analysis of sugars was developed by capillary zone electrophoresis (CZE) with indirect UV detection. A mixture of nine mono- and oligosaccharides was separated in about 20 minutes on a fused silica capillary in a highly alkaline (pH > 12) background electrolyte (BGE). With tryptophan as the marker detected at 280 nm the femtomole level detection of sugars was possible. The system was optimized by studies on the buffer pH, the marker concentration, as well as the inner diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 23 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Based on the fundamental transport equations using the eigenvector approach, Poppe's research group [21,221 have introduced a mathematical model for the simulation of indirect detection electropherograms, in which the analyte peak directions, number and position of system peaks, and magnitudes of detector responses can be predicted based on the results of computational calculations. It has been reported that the simulated data showed deviations from experimental results in some indirect detection systems [16,231. However, studies on the detector response patterns in separations of mixtures containing both cationic and anionic analytes, regarding the influence of the charges of the marker ions and the composition of the BGEs, have not been reported in the literature to date according to our knowledge.…”
Section: Introductionmentioning
confidence: 88%
“…Based on the fundamental transport equations using the eigenvector approach, Poppe's research group [21,221 have introduced a mathematical model for the simulation of indirect detection electropherograms, in which the analyte peak directions, number and position of system peaks, and magnitudes of detector responses can be predicted based on the results of computational calculations. It has been reported that the simulated data showed deviations from experimental results in some indirect detection systems [16,231. However, studies on the detector response patterns in separations of mixtures containing both cationic and anionic analytes, regarding the influence of the charges of the marker ions and the composition of the BGEs, have not been reported in the literature to date according to our knowledge.…”
Section: Introductionmentioning
confidence: 88%
“…For the most challenging case of neutral carbohydrates, a charge can be endowed (i) by simple deprotonation in highly alkaline BGEs (pH > 12), allowing their separation according to their p K a values and size, and their subsequent detection by indirect absorbance using an anionic chromophore (e.g. sorbate , tryptophan or 2,6‐pyridine dicarboxylate ), or amperometry , (ii) by in‐capillary complexation of the carbohydrates with borate anions or alkaline earth cations, allowing their separation according to their complexing ability and size, and their detection under underivatized form by direct absorbance in the low‐UV range (borate complexes) or under appropriate precapillary derivatized form (borate and metal complexes), (iii) by precapillary labeling their reactive reducing end with a charged UV‐absorbing or fluorescent tag (e.g. 2‐aminopyridine, 6‐aminoquiniline, 1‐phenyl‐3‐methyl‐5‐pyrazolone, 8‐aminonaphtalene‐1,3,6‐trisulfonate, 8‐ (or 9‐) aminopyrene‐1,3,6‐ (or 1,4,6‐) trisulfonate (APTS)), allowing both their separation according to their size and sensitive detection .…”
Section: Introductionmentioning
confidence: 99%
“…[14] in CE analysis of inorganic ions. Several groups utilized indirect UV detection in CE of carbohydrates [15][16][17][18][19][20][21]. Several UV-absorbing compounds, such as sorbic acid, riboflavin, 5-sulfosalicylic acid, 1,2,4-tricarboxylbenzoic acid, 1-naphthylacetic acid, and trypotophan, were used as backround chromophores.…”
Section: Introductionmentioning
confidence: 99%